2021
DOI: 10.3390/plants10061202
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Element Uptake by Salt-Sensitive Crops under Combined NaCl and Cd Stresses

Abstract: To test an assumption that organic soil can ameliorate nutritional disorders associated with metal and salinity stresses, we exposed salt-sensitive strawberry and lettuce to four salinity (0–60 mM NaCl) and three contamination (0.3–5 mg Cd/kg) rates in peat (pHH2O = 5.5). The results showed that, even at 20 mM NaCl, salinity stress exerted a dominant effect on rhizosphere biogeochemistry and physiological processes, inducing leaf-edge burns, chlorosis/necrosis, reducing vegetative growth in crops; at ≥40 mM, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…1). Lettuce was found to be sensitive to salt above 40 mM NaCl, similar to other crops (Rai et al 2006, Samineni et al 2011, Ondrasek et al 2021 and leafy greens (Beltrão et al 1997). A reduction in leaf area, not the number, appeared to cause a decrease in fresh or dry biomass (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…1). Lettuce was found to be sensitive to salt above 40 mM NaCl, similar to other crops (Rai et al 2006, Samineni et al 2011, Ondrasek et al 2021 and leafy greens (Beltrão et al 1997). A reduction in leaf area, not the number, appeared to cause a decrease in fresh or dry biomass (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…al. [42] and Ondrasek et al [46] also observed a marked decrease in the K/Na ratio in lettuce. The retention of a high K/Na ratio is defined as a determinative trait in salt tolerance [47].…”
Section: The Influence Of Increasing Sodium Chloride Concentrations O...mentioning
confidence: 87%
“…The water regime is one of the components of plant adaptation to growing conditions. Violations of the water balance leads to overheating of plants to lethal temperatures, which must be taken into account when developing agrotechnical measures for growing plants [ 30 , 31 ]. In this experiment, red currant plants were artificially (under laboratory conditions) subjected to extreme temperatures during important periods of development: growth and ripening of berries.…”
Section: Resultsmentioning
confidence: 99%